Crystal Structure of Ruthenium Phthalocyanine with Diaxial Monoatomic Ligand: Bis(Triphenylphosphine)Iminium Dichloro(Phthalocyaninato(2-))Ruthenium(III). (11th October 2012) - Yu, Derrick Ethelbhert; Kikuchi, Akira; Taketsugu, Tetsuya; Inabe, Tamotsu
Abstract : Axially-ligated iron phthalocyanines have been found to be good molecular conductors with giant negative magnetoresistance (GNMR) which originates from a strong intramolecular π - d interaction between the metal and phthalocyanine. Ab initio theoretical calculations showed that substitution of ruthenium into the phthalocyanine complex would result in a significant increase in the π - d interaction of the system, potentially intensifying GNMR. This paper presents the crystal preparation and X-ray structural characterization of bis(triphenylphosphine)iminium dichloro(phthalocyaninato(2-))ruthenium(III), PNP [Ru III (Pc 2− )Cl2 ]. It is observed that [Ru III (Pc 2− )Cl2 ] system has a symmetric planar RuPc unit with perpendicular axial ligands which results in a unidirectional and uniform solid-state arrangement, suitable for π - d interaction-based molecular conductors with potentially exceptional GNMR.